The Effectiveness of Foreign Lecturers’ Teaching for Design Students - Мариям, Езиева Нехир (Рroblems of engineering and professional education, 2025)
This article examines the pedagogical effectiveness and cognitive impact of involving international faculty in teaching design students. The aim of the study is to determine how international teaching formats influence students’ academic engagement, professional reflection, and cognitive growth. The study employed a phenomenological approach using written reflections and semi-structured interviews as the main sources of data. One international faculty member and fifteen design students participated in the study. The results showed increased engagement, higher creative initiative, and deeper levels of professional thinking among students. Structured lesson formats, visual learning methods, and project-based learning improved knowledge acquisition. Initial language and cultural barriers gradually decreased, ensuring a smooth adaptation. The study shows that international faculty members make a positive contribution not only to academic outcomes, but also to students’ emotional, cognitive, and intercultural development. Moreover, the results indicate a high potential of this model in developing autonomous thinking, cultural flexibility, and learning competence based on visual cases. The author suggests the need for larger scale studies with mixed methodological approaches in future research.